Jubileusz czterdziestolecia Katedry Pedagogiki Wczesnoszkolnej i Pedagogiki Mediów Uniwersytetu Śląskiego w Katowicach – geneza, przemiany problematyki badań, granty, zamierzenia - Juszczyk, Stanisław (Chowanna, 2019)
The article is devoted to the analysis of scientific achievements of researchers and teachers of the Department of Early Childhood Education and Media Pedagogy of the University of Silesia in Katowice during forty years of its functioning in this academic centre. These achievements are presented against the background of the development of theoretical studies and empirical research conducted in leading academic centres in Poland in the field of preschool pedagogy, early-school pedagogy and media pedagogy.